JUSTIFICATION OF EVALUATION CRITERIA OF GOLD BENEFICIATION ABILITY BY GRAVITATIONAL METHODS - Alexandrova, Tatyana; Romashev , Artyem; Potemkin , Vadim (Journal of Applied Engineering Science, 2020)
The development of science and technology involves the use of specialized software packages designed, among other things, for mathematical modeling and simulation of enrichment processes. One of the goals of using this type of software is to optimize technological treatment processes, design of processing plants, etc. However, since the corresponding software is not always freely available, or it does not exist, there is a need to develop application tools. The objective is to study the application of object-oriented programming to evaluate the enrichment of raw materials by gravitational methods. This paper presents the results of mathematical modeling of the gravitational separation of a mixture of polymineral gold-pyrite, gold-quartz, and gold-arsenopyrite intergrown pieces. The obtained alignment charts allow estimating the enrichment of raw materials depending on the unlocking degree of intergrown pieces. As a result of the study, a criterion was proposed to evaluate the possibility of gravitational grain separation, grain size, and unlocking degree. A chart for evaluating the possibility of gravitational separation was proposed.